#TITLE_ALTERNATIVE# - KRISTIE (NIM : 12910037), MICHAEL
This research calculates the energy potential use of tidal currents in Raja Ampat, West Papua, Indonesia with simulation from hydrodynamic model. The 2 dimentional horizontal hydrodinamic model that was used is Delft3D. Geografic model area covers 129.850E Ã‚Â– 131.040E and 0.3600S - 1.160S with 175 x 125 meter grid. Model input consist of 9 tidal constituent (M2, K1, O1, K2, P1, N2, S2, Q1, Mf) in 4 open boundary condition acquired from TPXO7. Simulations were carried out for 30 days, starting from the 1st of April 2013 - 30 April 2013, with 36-second time steps. The results of the simulation are tidal current then calculated and mapped to obtain an estimate of the potential energy use from tidal currents in Raja Ampat with Gorlov turbine scheme (cut in speed 0.5 m.s). The tidal current at the time of spring tide in Mansuar Strait has a maximum current magnitude at 1.12 m/s moving towards east and the maximum current magnitude during neap tide is 0.64 m/s, also moving towards east. The highest current magnitude at Sagawin Strait is 1.8 moving toward east during spring tide. The highest power density from marine current located in the Sagawin Strait, during spring tide for 14 kW and during neap tide for 2.1 kW in Sagawin Strait. For 30 days of simulation Sagawin Strait produce 247.372 kW of power and turbine can work for 20 days. For 30 days of simulation Mansuar Strait produce 132 kW of power and turbine can work for 14 days. The place with the most potential for marine current turbine installation is Sagawin Strait located between Bantata Island and Salawati Island.